Urban Transitions and Regeneration: The Politics of Policy-making. - Čamprag, Nebojša (My University, 2021)
This cumulative habilitation thesis is composed of one book chapter and four peer-reviewed academic papers, written and published in the period between 2014 and 2019: (1) Urban regeneration as a collaborative effort – strategic responses; (2) The Trap within Anticipated Regrowth: Two Sides of Strategic Response to Urban Decline in Leipzig to shrinking cities in East Germany; (3) Innovative post-neoliberal policy as a way out of crisis? Another reflection on the case of urban decline in Detroit; (4) Re-imagineering Belgrade and Skopje: Urban Megaprojects between Politics and Struggle. (5) Monika Grubbauer/Nebojša Čamprag: Urban Megaprojects, Nation-state Politics and Regulatory Capitalism in Central and Eastern Europe: The Belgrade Waterfront Project. In the focus is the phenomenon of urban regeneration, perceived as a consequence of socioeconomic and political transitions.
Keywords: Stadterneuerung; Schrumpfende Stadt; Schrumpfung; Regeneration; Großprojekt; Entwicklungsmöglichkeit; Transformationsprozess; Bürgerinitiative; Sozioökonomischer Wandel; Wirtschaftswachstum; Kommunalpolitik; Postwachstum